2011
DOI: 10.1111/j.2041-1626.2011.00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of topical ozonated oil on the epithelial healing of palatal wound sites: a planimetrical and cytological study

Abstract: Our results showed significant improvement in wound size and epithelial healing after topical ozonated oil application compared to control oil on palatal wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
14

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 35 publications
1
54
0
14
Order By: Relevance
“…The application of ozonated water had accelerated the wound healing in the oral cavity within the first 48 hours as compared to placebo water, resulting in an earlier epithelial wound closure after 7 days. Our study also supports the findings of Patel et al, [2,10,12] where an improved healing was found after one week of the ozone application.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The application of ozonated water had accelerated the wound healing in the oral cavity within the first 48 hours as compared to placebo water, resulting in an earlier epithelial wound closure after 7 days. Our study also supports the findings of Patel et al, [2,10,12] where an improved healing was found after one week of the ozone application.…”
Section: Discussionsupporting
confidence: 93%
“…Which it readily dissolves in water, it generates hydrogen peroxide and lipoperoxides, which can explain its prolonged disinfectant and stimulatory activity on ulcerated chronic wounds [4]. Moreover, the phenomenon of an improved wound healing after the ozone therapy has been related to the rapidly changing cell types and to the release of cytokines that modulate the complex healing process [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozone gas dissolved in plant oils, such as olive oil, is being discussed in dentistry for its excellent antimicrobial property, without the development of drug resistance and facilitation of wound healing [26][27][28][29] . In orthodontics, clinicians tend to seek out an effective antimicrobial agent to apply prior to bracket bonding in order to prevent dental caries during fixed appliance treatment [30][31][32][33][34] .…”
Section: Volume 41 -June 2012mentioning
confidence: 99%